Fenomena Penggunaan Pakaian Menutup Aurat Dengan Desain Ketat Dalam Perspektif Sosiologi Agama: Studi Kasus Pada Mahasiswi Universitas Islam Negeri Sumatera Utara - Suri, Atika; Jannah, Dina Miftahul; Salsabila, Danish Ara; Kinasih, Rizki; Pulungan, Fahrur Rozy; Yudha, Sandy (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This study aims to analyze the phenomenon of intimate clothing with tight designs among UINSU female students, as well as the factors that influence their understanding of Islamic clothing. Using a qualitative approach with observation, interview, and documentation techniques, this study revealed that many female students understand Islamic clothing as an obligation to cover their intimate parts without considering aspects of modesty. The influence of social media and modern fashion trends also play a major role in shaping their clothing style. This study concludes that a deeper understanding of the values of Islamic dress is needed to maintain a balance between religiosity and modernity.